Flexibilidade versus proteção trabalhista : uma análise de 152 países e suas interações com o desenvolvimento humano e socioeconômico - Prado, Altevir Dias do (2018)
The labor market occupies a prominent place in economic studies, since it establishes the labor relations, being the meeting point between companies and workers, determining for the functioning of the economy as a whole and for development. In this thesis, models of labor market organization, both the most flexible and the most protective, will be discussed. The research problem consists in seeking subsidies that allow to elucidate which labor legislation is most recommended, be it in the scope of economic growth and development, or in the fulfillment of the desires and desires of the individuality of the worker. To do so, we analyzed data on labor legislation adopted by 152 countries and constructed an indicator of protection, which is the first objective of the thesis. The information on protection was confronted with socioeconomic indicators such as unemployment, income, inequality and human development, which is the second objective of the thesis. These variables served as indicators to identify the most appropriate options, especially for the worker, in view of social welfare, growth and economic development. The results found tend to organize a ranking of countries among the most protective and the most flexible. They also allowed dividing the regions and continents between protective and flexible. It was observed a densification around the median in terms of levels of protection and correlated comparative analyzes allowed to identify the relationship between labor legislation and socio-economic indicators.